Epidemiology of carbapenem-resistant Enterobacteriaceae: A 5-year experience at a tertiary care hospital - Darunee Chotiprasitsakul (2020)
© 2019 Chotiprasitsakul et al. Purpose: The incidence of carbapenem-resistant Enterobacteriaceae (CRE) has been increasing worldwide. Ertapenem resistance is mediated by non-carbapenemase mechanisms, and has less of an effect on susceptibility to imipenem and meropenem. This study aimed to study the epidemiology of CRE, and to compare risk factors and related mortality between nonsusceptibility to ertapenem alone Enterobacteriaceae (NSEE), with non-susceptibility to other carbapenems (imipenem, meropenem, or doripenem) Enterobacteriaceae (NSOCE) at a tertiary care hospital in Thailand. Methods: All CRE isolated were identified between December 2011 and December 2016. Quarterly incidence rate was estimated. Hospital-wide carbapenem consumption was calculated as defined daily doses (DDD). Relationships between hospital-wide carbapenem consumption and incidence of CRE were tested. Factors associated with NSEE and NSOCE, and risk factors associated with 14- and 30-day mortality in patients with CRE infection were determined. Results: The quarterly CRE incidence increased significantly from 3.37 per 100,000 patientdays in the last quarter of 2011 to 32.49 per 100,000 patient-days in the last quarter of 2016. (P for trend <0.001). Quarterly hospital-wide carbapenem consumption increased 1.58 DDD per 1,000 patient-days (P for trend=0.004). The Poisson regression showed the expected increase of CRE incidence was 1.02 per 100,000 patient-days for a 1 DDD per 1,000 patient-days increase in carbapenem consumption (P<0.001). There were 40 patients with NSEE and 134 patients with NSOCE in the 5-year study period. The NSEE group had significantly lower carbapenem exposure compared with the NSOCE group (adjusted odds ratio: 0.25; P=0.001). No difference in 14-day and 30-day all-cause mortality between the two groups was observed. Conclusion: The incidence of CRE has risen significantly at our institution. Previous carbapenem use was associated with NSOCE. This hospital-wide carbapenem use was significantly associated with the increasing incidence of CRE.